The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1021/bk-1995-0582.ch025
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Potential Use as Herbicides

Abstract: There is great incentive to discover effective and economically feasible herbicides that are toxicologically and environmentally benign.Several hundred active ingredients of herbicides are now sold world-wide. Virtually all of these compounds were discovered by screening compounds from organic chemical synthesis programs.Leads for the structure of one group of patented herbicides came from 1,8-cineole, a well known plant allelochemical. However, plants have thus far not been as lucrative as microbial products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
(49 reference statements)
0
16
0
2
Order By: Relevance
“…It has been shown previously that some plant VOCs have an eVect on the growth and seed germination of other plants Asplund 1968;Duke and Abbas 1995). Bate and Rothstein (1998) showed that aerial trans-2-hexenal quantitatively reduced Arabidopsis seed germination and root growth, similar to methyl jasmonate.…”
Section: (C)mentioning
confidence: 89%
“…It has been shown previously that some plant VOCs have an eVect on the growth and seed germination of other plants Asplund 1968;Duke and Abbas 1995). Bate and Rothstein (1998) showed that aerial trans-2-hexenal quantitatively reduced Arabidopsis seed germination and root growth, similar to methyl jasmonate.…”
Section: (C)mentioning
confidence: 89%
“…Many secondary compounds of plants, microorganisms and lichens are known to be toxic to insect, microbes and other organisms. Many of these compounds have been used successfully, either in their natural or a modified form, as inseticides, fungicides and herbicides (Duke and Abbas, 1995). Phenolic substances are included in this group and an example is the herbicide "Letharal" -phytotoxic fraction of Lethariella canariensis.…”
Section: Introductionmentioning
confidence: 99%
“…Essas toxinas podem agir sinergicamente com outras atividades do patógeno, desde que invada o tecido das plant as. Suas utili zações diret as como bioerbicidas ou como estrutura básica para o desenvolvimento de novas classes de herbicidas vêm recebendo cada vez mais atenção, não só por parte da comunidade científica, mas também pelas empresas que se dedicam à produção de defensivos agrícolas (Duke & Abbas, 1995;Hoa gla nd, 1990). Alg uns traba lho s for am desenvolvidos nos últimos anos visando identificar e caracterizar a atividade biológica de toxinas produzidas por fungos (Gerwick et al, 1997;Strobel et al, 1991;Duke et al, 2002;Metha & Brognin, 2000).…”
unclassified